PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS DISCOVERY LEARNING PADA MATERI BANGUN RUANG SISI LENGKUNG KELAS IX SMP NEGERI 16 PADANG - Agiestina Nasution (Departemen Matematika, 2022)
The potential to understand mathematical concepts of students at SMPN 16 Padang is very low. This is because students have not been facilitated by learning media that builds understanding of students' concepts. One of the methods used is to develop learning media in the form of Discovery Learning-Based Student Worksheets (LKPD). This study aims to develop Student Worksheets (LKPD) Based on Discovery Learning on the material of Constructing Curved Side Spaces for class IX SMP/MTs. The developed Student Worksheet (LKPD) is assessed based on legitimate and practical. This study is categorized as design research using the Plomp development model which consists of three stages, namely initial investigation, development/prototyping stage and assessment stage. At the initial investigation stage, needs analysis, curriculum analysis, concept analysis, and student analysis were carried out in order to obtain the characteristics form learning media developed. At the stage of development or prototyping, LKPD is designed with three characteristics, namely interface (display), content (content), and support (language and readability). The results obtained are at the LKPD validation stage, namely obtaining a score of 3.25 with a very valid category. In the practicality stage, the practicality value was obtained with a score of 3.14 in the practical category. So that it can be concluded that the Student Worksheet (LKPD) based on Discovery Learning is valid and practical to use in learning. Keywords - desain research, BRSL, Discovery Learning